Pengelolaan Instagram @bawasludkijakarta Sebagai Bentuk Kegiatan Digital PR - Salsabila, Fahita Putri Putri; Risdayah, Enok; Astuti, Dyah Rahmi (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
Bawaslu of DKI Jakarta Province is a non-ministerial government agency that focuses on the electoral field. Instagram @bawasludkijakarta management is part of digital PR activities in the 5.0 era which previously did not get interest from the public. This study aims to describe the stages of Instagram management managed by the Public Relations of the Bawaslu Province of DKI Jakarta. The concept in this study uses The Circular Model of Some, constructivism paradigm, interpretive approach, and uses descriptive methods. The results of the research prove that the Instagram @bawasludkijakarta management process run by the Public Relations of the Bawaslu Province of DKI Jakarta is carried out in four stages (1) share which includes the process of disseminating information through the aspects of participate, connect, and build trust. (2) optimize through communication planning & message optimization. (3) manage through media monitoring & evaluation process. (4) engage to measure the achievement of content to the public.